Penggunaan Multimedia History Virtual Exhibition Untuk Melatih Kemampuan Historical Thinking Siswa SMAN 1 Batang Anai - Hastuti, Hera; Rusdi, Rusdi; Fithriah, Rahmuliani; Kamila, Mufti; Suprina, Nurlis (Jurnal Kronologi, 2024)
Historical Thinking is one of the main objectives in learning history. Building Historical Thinking in students has its own challenges for history teachers, in addition to limited knowledge, also because so far there is no specific strategy that can be used by teachers in fostering Historical Thinking. Applying virtual reality multimedia in the form of History Virtual Exhibition (HVE) to improve students' Historical Thinking ability is the main objective of this research. Using descriptive quantitative method, this research was conducted at SMAN 1 Batang Anai West Sumatra. Using purposive sampling technique in class XI Phase F obtained 57 samples. Using a questionnaire as a data collection instrument, an average score of 3.04 was obtained from the highest scale of 4. As for the questionnaire given to two history teachers from the same high school, an average score of 3.38 was obtained. From the results of this study it can be concluded that the use of HVE as a multimedia history learning is effective for improving students' Historical Thinking skills.